Intrinsic impacts of the expression of PD-L1 on postoperative recurrence in EGFR-mutated lung adenocarcinoma - Ito, Atsushi; Kano, Shu; Tarukawa, Tomohito; Suzuki, Yuta; Sakaguchi, Tadashi; Ito, Kentaro; Nishii, Yoichi; Taguchi, Osamu; Yasui, Hiroki; Takao, Motoshi; Hataji, Osamu (Frontiers in Oncology, 2024)
Objectives This study aimed to assess the intrinsic impacts of the expression of PD-L1 on postoperative recurrence and the prognosis in patients with epidermal growth factor receptor (EGFR)-mutated lung adenocarcinomas. Patients and methods Data from 221 surgically resected pathological stage IA–IIIA lung adenocarcinomas, collected between 2017 and 2019, were analyzed. This included measurements of EGFR mutations and the PD-L1 expression. Recurrence-free survival (RFS) and overall survival (OS) were estimated using a Kaplan-Meier analysis and log-rank test. The independent risk factors for RFS were assessed using univariate and multivariate analyses. Results Among the patients, 140 were PD-L1-negative (<1%), while 81 were PD-L1-positive (≥1%). PD-L1 positivity was significantly associated with male sex (p=0.038), smoking habit (p=0.005), ND2 lymph node dissection (p=0.013), higher malignant subtype (p=0.003), higher histological grade (p=0.001), and advanced pathological stage (p=0.004). Conversely, EGFR mutations were more common in the PD-L1-negative group than in the PD-L1-positive group (p=0.006). Patients were categorized into four groups based on their EGFR mutation status and PD-L1 expression status: PD-L1-positive (≥1%) with or without EGFR mutations (EGFR(+)/PD-L1≥1% or EGFR (–)/PD-L1≥1%), and PD-L1-negative (<1%) with or without EGFR mutations (EGFR(+)/PD-L1<1% or EGFR (–)/PD-L1<1%). Among these groups, EGFR(+)/PD-L1≥1% cases exhibited the worst 5-year RFS (log-rank, p=0.010), while there was no significant difference in 5-year OS (log-rank, p=0.122). Furthermore, a multivariate analysis revealed that PD-L1 positivity was an independent significant factor for RFS in EGFR-mutated lung adenocarcinoma (p=0.013). Conclusion PD-L1 positivity emerged as an independent risk factor for RFS in patients with EGFR-mutant resected lung adenocarcinoma. These findings may provide valuable insights into the prognostic impact of PD-L1 expression and guide the implementation of postoperative adjuvant therapy in this patient population.